Cover Feature: Behavior of Ru–bda Water‐Oxidation Catalysts in Low Oxidation States (Chem. Eur. J. 49/2018). Issue 49 (1st August 2018) - Matheu, Roc; Ghaderian, Abolfazl; Francàs, Laia; Chernev, Petko; Ertem, Mehmed Z.; Benet‐Buchholz, Jordi; Batista, Victor S.; Haumann, Michael; Gimbert‐Suriñach, Carolina; Sala, Xavier; Llobet, Antoni
Abstract : Multiple equilibria are involved in Ru‐bda based complexes in aqueous solutions at low oxidation states. These equilibria are pH‐dependent and are the key for understanding the generation of Ru active species at high oxidation states, which are responsible for water oxidation catalysis. More information can be found in the Full Paper by A. Llobet, V. Batista, C. Gimbert‐Suriñach, X. Sala, et al. onpage 12838 .